Dual‐Polarized Tri‐Channel Encrypted Holography Based on Geometric Phase Metasurface. Issue 2 (19th October 2020) - Wang, Yue; Guan, Chunsheng; Li, Haoyu; Ding, Xumin; Zhang, Kuang; Wang, Jinxiang; Burokur, Shah Nawaz; Liu, Jian; Wu, Qun
Abstract : Metasurface‐based encrypted holography has drawn much attention recently due to its excellent ability in storing/displaying information with good security. To enhance the encryption security of metasurface holograms, multiplexing techniques, for which a large number of parameters need to be scanned to achieve the desired meta‐atoms, are highly demanded. Herein, a metasurface design scheme, which utilizes solely geometric phase elements to manipulate both co‐ and cross‐polarized reflected fields independently, is proposed. Using an improved weighted Gerchberg–Saxton (GSW), a holographic algorithm is proposed for 1‐bit phase, dual‐polarized tri‐channel encrypted metamirrors. Proof‐of‐concept prototypes are fabricated and experimental demonstrations are performed at microwave frequencies. Simulations and measurements are carried out to validate the proposed design, and the results agree well with the theoretical design scheme. Such dual‐polarized and tri‐channel encrypted metamirrors are appealing for applications in polarimetric imaging, information encryption/storage and beam splitting, shaping and steering. Abstract : A metasurface design scheme, which utilizes solely geometric phase elements to manipulate both co‐ and cross‐polarized reflected fields independently, is proposed. Using the scheme, a dual‐polarized tri‐channel encrypted metamirrors are designed. Such metamirrors are appealing for applications in polarimetric imaging, information encryption/storage and beam splitting, shaping and steering.